No contrapeso da modernidade: A Casa de Cultura Cavaleiro de Jorge e o Encontro de Culturas Tradicionais da Chapada dos Veadeiros, Goiás (2001-2023) - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The study addresses the historical and cultural relevance of the Cavaleiro de Jorge Cultural Center and the Meeting of Traditional Cultures of Chapada dos Veadeiros, focusing on the preservation of the cultural traditions of the traditional peoples of the region. Entitled “In the Counterweight of Modernity: The Cavaleiro de Jorge Cultural Center and the Meeting of Traditional Cultures of Chapada dos Veadeiros, Goiás (2001-2023)”, it permeates the processes of resistance to Modernity, highlighting the maintenance of traditional knowledge during and after the event. The objectives include analyzing the social and cultural importance of the House, the influence of Modernity on popular cultures and the organization of the Meeting of Cultures, which takes place from 2001 to 2023. The methodology involves qualitative analysis, reading of documents, field research and participant observations with organizers and participants. The hypothesis suggests that the event, promoted by the Cultural Center, is a form of cultural resistance, involving the participation of diverse groups and contributing to the transmission of traditions in Goiás society. Furthermore, the dissertation highlights the relevance of the Casa de Cultura not only in the Cerrado, but throughout Brazil, due to the scarcity of spaces dedicated to cultural preservation
Counterweight to modernity: The Cavaleiro de Jorge Cultural Center and the Meeting of Traditional Cultures of Chapada dos Veadeiros, Goiás (2001- 2023)
Keywords: Casa de Cultura - Povos Tradicionais; Culturas Tradicionais - Modernidade; Cultural Center - Traditional Peoples; Traditional Cultures - Modernity; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::ANTROPOLOGIA